HADITH AND INDONESIA POLICIES ON FEMALE REPRODUCTIVE HEALTH: AN INTERDISCIPLINARY STUDY FROM MEDICAL AND ISLAMIC PERSPECTIVES - Monady, Hanief; Baihaki, Baihaki; Widagdo, Haidi Hajar; Hidayat, M. Rifqi (Khazanah: Jurnal Studi Islam dan Humaniora, 2025)
This study explores the intersection of Islamic teachings, bioethical principles, and state regulations in addressing women’s reproductive health, focusing on Hadith, MUI fatwas, and Indonesian legal frameworks. The research aims to examine how these three normative authorities—religion, medicine, and law—interact to construct an ethical discourse that safeguards women’s dignity, autonomy, and well-being. The urgency of this study lies in the ongoing tension between traditional religious interpretations and contemporary medical ethics, which increasingly demand a contextualized and humane approach to reproductive health issues such as menstruation, contraception, abortion, and early marriage. Methodologically, this research employs a qualitative-descriptive approach through textual and discourse analysis, utilizing Michel Foucault’s discourse theory as an analytical lens to uncover the dynamics of power and knowledge in regulating women’s bodies. The study systematically examines classical Hadith texts, fatwas issued by the Indonesian Ulema Council (MUI), and national laws related to reproductive health and marriage, integrating them within the framework of modern bioethical principles—beneficence, non-maleficence, autonomy, and justice. The findings reveal that Islamic bioethics demonstrates a harmonization between moral-religious values and scientific rationality. The study concludes that a holistic bioethical approach, integrating religious, medical, and legal dimensions, is essential for developing a more just, contextually grounded, and ethically coherent framework for women’s reproductive health in Muslim societies, while contributing to global ethical discourse on gender and health.